#TITLE_ALTERNATIVE# - ALDIREZA FIRMANSYAH (NIM 13703001), R.M.
The rapid advances in computer development had facilitated the development of modeling in all aspects. In technical aspects, sometimes there problems that is too complex that it needs to be solved numerically. One method frequently used by engineers is finite element method. Finite element method is very helpful in material science, especially in solid mechanics. This method can help to predict stress and strain in complex systems. An example of the application of this method is in the prediction of the behavior of two phase material when we apply stress. Dual-phase steel (ferrite-martensite) is an example of two phase material. The mechanical properties dual phase steel are determined by many factors, some of them are mechanical property, fraction, and morphology of each phase. Simulation using FEM can create a model that can predict the behavior of dual phase steel under the application of stress. By varying the martensite volume fraction, yield strength, and morphology, we can build a curve of varying flow stress. Observation of the curves gives that the variation in martensite morphology results in the variation in mechanical properties at constant martensite volume fraction and yield strength. It is also observed that the increase in martensite yield strength and volume fraction can increase the strength of dual phase steel. This result fits the Law of mixture.